Normal values for body composition in adults are better represented by continuous reference ranges dependent on age and BMI. Issue 5 (May 2023) - Enderle, Janna; Reljic, Dejan; Jensen, Björn; Peine, Sven; Zopf, Yurdagül; Bosy-Westphal, Anja
Summary: Background & aims: Reference values for body composition parameters like skeletal muscle mass index (SMI) depend on age and BMI. To ensure reference intervals reflect these changes, they have traditionally been separated into groups of young adults based on sex and BMI. However, this static stratification oversimplifies the dynamic and gradual changes of body composition with increasing age and BMI. The aim was therefore to provide continuous reference ranges for body composition parameters. Methods: Cross-sectional data of 1958 healthy men and women with an age between 18 and 97 years and a BMI between 17.1 und 45.6 kg/m 2 were obtained between 2011 and 2019. Multiple regression analyses stratified by sex with age, age 2 and BMI as independent variables were conducted to predict fat mass index (FMI), visceral adipose tissue (VAT), SMI, appendicular lean soft tissue index (ALSTI) and the ratio between extracellular to total body water (ECW/TBW). Results: The regression models explained between 61 (VAT in women and ALSTI in men) and 93% of the variance in the respective body composition parameters (FMI in women). Age had only a minor impact (2–16%) whereas BMI substantially increased the explained variance of reference models for FMI, VAT and ALSTI (total explained variance 61–93%). In SMI, age is a major determinant of the explained variance (36% in men and 38% in women) with BMI equally contributing to the explained variance (total explained variance 72% in men and 75% in women). For ECW/TBW-ratio, age nearly completely explained the variance (79% in men and 74% in women) whereas BMI added only 2–3% to the explained variance. Conclusions: In conclusion, the derived continuous reference ranges are expected to improve body composition evaluation especially in very overweight and very old persons. Future studies applying these reference equations need to validate these assumptions. Study registration, clinicaltrials.gov: NCT01368640, NCT01481285, NCT03779932, NCT 04028648.